Learning to teach in higher education - Paul Ramsden (Routledge, 1995)
This book addresses the problem of how best to evaluate and improve the standard of teaching in higher education in a climate of accountability and appraisal. Linking educaional theory with the practical realities of teaching, it argues that becoming an effectice teacher in higher education involves listening to students and changing how we think about the teaching